A Sleep Scheduling Mechanism with PSO Collaborative Evolution for Wireless Sensor Networks. (11th March 2015) - Dong, Luobing; Tao, He; Doherty, William; Young, Marten
Abstract : To extend the lifetime of a wireless sensor network and improve the energy efficiency of its nodes, it is necessary to use node collaborative sleep algorithm to reduce the number of redundant nodes in the network. This paper proposes a particle swarm optimization sleep scheduling mechanism for use in wireless sensor networks based on sleep scheduling algorithm. The mechanism adopts the approach of density control and finds the redundant nodes based on the computation results of the network coverage. Experimental results show that the proposed algorithm can ensure adequate coverage under the premise of the ability to close off the redundant nodes, while reducing the total energy consumption of the network.